Analisis Vegetasi Tumbuhan Gunung Lawu Jalur Pendakian Cemoro Mencil Girimulyo Jogorogo Ngawi - ROSADI, IHWAN; , Dr. Siti Chalimah, M.Pd (2015)
Lawu Mountain is a mountain located on the border between Central Java and East Java. This mountain has an altitude of 3265 m.asl. Geographically located around 111o15' E dan 7o30'S. The purpose of this study was to determine the types of plants and know the diversity index and dominance found in Lawu Mountain along the hiking trails of Cemoro Mencil Girimulyo Jogorogo District Ngawi Regency at an altitude of 1.600 m.asl, 2.200 m.asl and 2.800 m.asl. This study used a sample survey method. The results discovered 12 orders, 14 families, 16 genera which include 17 species of plants that spread at an altitude of 1.600 m.asl, 2.200 m.asl and 2.800 m.asl in Lawu Mountain along the hiking trails of Cemoro Mencil Girimulyo Jogorogo District Ngawi Regency. At an altitude of 1.600 m.asl obtained 7 numbers collection which includes 6 families and 7 plant species have been inventoried. At an altitude of 2.200 m.asl obtained 9 numbers collection which includes 7 families and 9 species of plants have been inventoried. And at an altitude of 2.800 m.asl obtained 9 numbers collection which includes 8 families and 9 species of plants have been inventoried. Based on the results of this study concluded that the diversity of plants in Lawu Mountain along hiking trails Girimulyo Jogorogo District Ngawi Regency including low.